Association of maternal bitterness sensitivity to 6-n-propylthiouracil with dental caries experience in mothers and their preschool children - Shina Gandotra; Ullal Anand Nayak; Sudhindra M. Baliga; Prathibha Anand Nayak; Bharat Ahuja (Journal of Indian Society of Pedodontics and Preventive Dentistry, 2025)
Context: Oral health is shaped by a combination of genetic, dietary, and behavioral factors, with bitterness sensitivity being one genetic trait that may influence oral health behaviors. Aims: This study aims to explore the link between maternal taste perception and dental caries in both mothers and their preschool-aged children. Methods: A cross-sectional observational study was carried out with 172 mother-child pairs, including children aged 2–3 years. The study employed a convenience sampling method, selecting participants from those visiting the pediatric dentistry outpatient department. Data collected included demographics, caries experience (DMFT/dmft indices), and taste preferences. Maternal bitterness sensitivity was assessed using a 6-n-propylthiouracil (PROP) test and categorized using the Green Labeled Magnitude Scale into supertasters, medium tasters, and nontasters. Statistical Analysis: A comparative analysis between groups (supertasters, medium tasters, and nontasters) was conducted using analysis of variance. Pearson’s correlation was used to assess the relationship between the caries experience of mothers and their children. A significance level of P < 0.05 was used for all statistical tests. Results: Nontaster mothers had significantly higher caries experience than supertasters and medium tasters, and their children similarly showed higher caries rates (P < 0.05). A positive correlation was observed between maternal and child caries experience, while a negative correlation was found with PROP scores. Maternal taste perception was also associated with children’s sweet preferences. Conclusion: Maternal bitterness sensitivity is associated with poorer oral health in both mothers and children, influencing caries experience and sweet preferences.